United Kingdom-Montserrat-British Overseas Territory : 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2012)
The 2011 Article IV Consultation highlights that low growth is expected for Montserrat in 2011 after sharp output contractions in 2009-10. Stress in the financial sector and slower-than-expected development of major capital investment projects continue to limit prospects for growth. Directors have welcomed the development of a strategy for addressing financial vulnerabilities and the initial progress in implementing it. They have supported preemptive action to minimize costs and risks and preparation of an action plan spelling out the roles of key players.